Penser l’accompagnement linguistique des personnes migrantes en Suisse romande - Anne-Christel Zeiter (Recherches en didactique des langues et des cultures)
The language training of adult migrants poses an almost insoluble equation today, in French-speaking Switzerland as elsewhere: if we consider the professionalization of this field to be desirable and necessary, for various reasons which will be dealt with here, how can we achieve this without losing the volunteers who wish to become involved? And why is volunteering so important in this context? This article provides an overview of language training in French-speaking Switzerland and identifies the administrative, legal, and political issues that influence its organization, both in training for trainers and the mobilization of volunteers. It concludes with a proposal that could contribute to solve this initial equation by shifting the focus from the status of language training actors to differentiated service objectives.